Review of the effects of energy crops on hydrology. - Stephens, William; Hess, Tim M.; Knox, Jerry W. (Cranfield University, 2001)
1) MAFF has recently launched a scheme to support the expansion of the area of energy crops grown in England in order to meet the nation’s Kyoto targets for the reduction in CO2 emissions. This has highlighted concerns about the possible effects of willow short rotation coppice (SRC) and Miscanthus on the hydrology of catchments in which they are grown. High levels of water use by these crops could result in less surface runoff, decreased aquifer recharge and hence reduced stream flow (Chapter 1